Does Dis/ability Now Sit at the Table(s) of Social Justice and Multicultural Education? - A Descriptive Survey of Three Recent Anthologies - Connor, David (Disability Studies Quarterly, 2012)
Keywords: disability, diversity, culture, social justice In this paper I contemplate the recent inclusion of disability within three contemporary diversity-based anthologies on social justice and multicultural education: Diversity and Multiculturalism: A Reader (2009), The Handbook of Social Justice in Education (2009), and Social Justice Pedagogy Across the Curriculum (2010). Using a macro analysis of each book and a micro analysis of ninety-nine chapters in total, I analyze emergent themes and contemplate ways in which disability is framed within broader conceptions of social justice and notions of multiculturalism. Additionally, I discuss the implications for Disability Studies in Education being included within these anthologies on social justice and multicultural education, and describe potential areas of interdisciplinary growth within policy, theory, research and practice.